Професійна підготовка рятувальників у Львівському державному університеті безпеки життєдіяльності (середина ХХ – початок ХХІ ст.) - Іванів, Ольга (Видавництво Львівської політехніки, 2013)
Изложены результаты анализа организации подготовки спасателей во Львове на разных этапах становления ведомственного учебного заведения. Выделены главные отличия этапов становления ведомственного учебного заведения. Установлено, что процесс развития образовательных стандартов в системе Болонского процесса не обошел и учреждений, осуществляющих подготовку спасателей. The author states the results of the rescuers training organization in Lviv at different stages of departmental education institution establishment. The article highlights the major differences between the stages of departmental education institution establishment. It is determined that the process of the development of educational standards in the Bologna process have not omitted the institutions that train rescuers.
Профессиональная подготовка спасателей во Львовском государственном университете безопасности жизнедеятельности (средина ХХ в. – начало XXI в.)
Professional training of rescuers at Lviv State University of Vital Activity Safety (middle of the XXth century – the beginning of the XXI century)
Keywords: подготовка спасателей; учебное заведение; образование; сравнительный анализ; учебный процесс; rescuers training; education institution; education; comparative analysis; learning process